Nuclear Fusion - Morse, Edward (Graduate Texts in Physics,, 2018)
The pursuit of nuclear fusion as an energy source requires a broad knowledge of several disciplines. These include plasma physics, atomic physics, electromagnetics, materials science, computational modeling, superconducting magnet technology, accelerators, lasers, and health physics. Nuclear Fusion distills and combines these disparate subjects to create a concise and coherent foundation to both fusion science and technology. It examines all aspects of physics and technology underlying the major magnetic and inertial confinement approaches to developing nuclear fusion energy. It further chronicles latest developments in the field, and reflects the multi-faceted nature of fusion research, preparing advanced undergraduate and graduate students in physics and engineering to launch into successful and diverse fusion-related research. Nuclear Fusion reflects Dr. Morse's research in both magnetic and inertial confinement fusion, working with the world's top laboratories, and embodies his extensive thirty-five year career in teaching three courses in fusion plasma physics and fusion technology at University of California, Berkeley. Combines theory, experiments, and technology into a single teaching text and reference Written in a concise style, accessible to both physicists and engineers Presents computation on an equal footing with analytic theory Emphasizes the underlying basic science for all of the material presented Dr. Edward Morse is Professor of Nuclear Engineering at the University of California, Berkeley. He has authored over 140 publications in the areas of plasma physics, mathematics, fusion technology, lasers, microwave sources, neutron imaging, plasma diagnostics, and homeland security applications. For several years he operated the largest fusion neutron source in the US. Frequently consulted by the media to explain the underlying science and technology of nuclear energy policy and events, Dr. Morse is also a consultant and expert witness in applications of fusion neutrons to oil exploration.